Activating Students Speaking Ability through English Dialogue Video - Apriyana Melly I. M.; Samtidar Samtidar; Amirullah Abduh (Journal of Excellence in English Language Education, 2023)
The purpose of this study was to determine the use of English dialogue video on students’ speaking ability. This research method was a pre-experimental design. The population of this research was the tenth-grade students of SMAN 2 Jeneponto in the academic year of 2022/2023 through a random sampling technique. There were 35 students from X MIPA 2 selected as the sample of this research. The instrument of this research was an English dialogue test to be delivered as the pre-test and post-test and recording to record the dialogue test. The research finding showed that using English dialogue video was significant to activate students’ speaking ability. It was proven by the mean score of the students’ pretest was 5.26 and the mean score of the students’ post-test was 6.87. From that data, it could be concluded that the use of English dialogue videos could activate students’ speaking ability.